2021
DOI: 10.3389/fmars.2021.637483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Uncertainties in Reconstructing the Pre-eutrophic State of the North Sea

Abstract: The North Sea is affected by eutrophication problems despite the decreasing riverine nutrient fluxes since the late 1980s. Formally, assessment of the eutrophication state of European marine environments is based on their historical state. Model estimates are increasingly used to support monitoring data that often do not encompass such pre-eutrophic conditions. However, various sources of uncertainties emerge when producing these estimates. In this study, we systematically quantify various sources of uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Using back‐tracking modelling approaches, some studies (e.g. Kerimoglu et al, 2018; Stegert et al, 2021) have shown a much lower phytoplankton biomass in the pre‐industrial nutrient‐poor coastal system. However, this type of approach does not allow the study of the taxonomic composition, and even less functional structure, but instead treats the phytoplankton community as a whole, either using chlorophyll a concentration or total abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Using back‐tracking modelling approaches, some studies (e.g. Kerimoglu et al, 2018; Stegert et al, 2021) have shown a much lower phytoplankton biomass in the pre‐industrial nutrient‐poor coastal system. However, this type of approach does not allow the study of the taxonomic composition, and even less functional structure, but instead treats the phytoplankton community as a whole, either using chlorophyll a concentration or total abundance.…”
Section: Discussionmentioning
confidence: 99%
“…This study found differences in historical coastal DIP loads (compared to JMP-EUNOSAT) up to ~10%. Stegert et al (2021) used estimates of historical river inputs from both MONERIS and E-HYPE and compared their influence on the nutrient and chlorophyll-a concentrations in the North Sea. They found higher marine nutrient concentrations, particularly in coastal zones, if the E-HYPE values were applied, with coastal zone DIP differences of 40% in the German Bight.…”
Section: Pre-eutrophic Scenariomentioning
confidence: 99%
“…For P loads, E-HYPE percentage results were used for most rivers, but for some rivers alternative estimates were used. Due to large differences between E-HYPE and the finer scale catchment models, and uncertainty in the E-HYPE P load estimation (Donnelly et al, 2013;Stegert et al, 2021), its historic P load percentages were replaced for rivers where alternative, more detailed information was available, as follows. The Danish authorities, basing their estimates on Timmermann et al ( 2021) set their pre-eutrophic P loads at 36% of current day loads for all Danish rivers.…”
Section: Pre-eutrophic Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…However, Contracting Parties used different approaches in establishing reference conditions to derive these values, leading to variable assessment levels and different outcomes of the eutrophication assessment across national borders (OSPAR, 2003b(OSPAR, , 2008b(OSPAR, , 2017. OSPAR recognized these limitations and requested the ICG-EMO working group to develop a coherent assessment framework across Contracting Parties that share assessment areas (Blauw et al, 2019;Gohin et al, 2019;Stegert et al, 2021).…”
Section: Harmonizing Assessment Levelsmentioning
confidence: 99%